2024
DOI: 10.1038/s41598-023-50582-7
|View full text |Cite
|
Sign up to set email alerts
|

Association between cataract and fatty liver diseases from a nationwide cross-sectional study in South Korea

Kyoung Hae Kang,
Daeun Shin,
Ik Hee Ryu
et al.

Abstract: This study examined the link between fatty liver disease (FLD) and cataracts, as previous research has suggested that FLD may contribute to metabolic syndrome, systemic inflammation, and potentially cataracts. We studied a nationwide cross-sectional cohort of the Fifth Korean National Health and Nutrition Examination Survey 2010–2011. FLD was defined as nonalcoholic FLD (NAFLD) and metabolic dysfunction-associated FLD (MAFLD). Multinomial logistic regression was utilized to investigate the relationship between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…In a Korean study ( 24 ), it was found that metabolism-associated fatty liver disease (MAFLD) was more closely associated with cataracts than non-alcoholic fatty liver disease (NAFLD). MAFLD may be a combined risk factor for cataracts, with significant correlations with all cataract subtypes because cataracts can be caused by various metabolic and inflammatory conditions, and MAFLD covers alcohol-induced cirrhosis and various metabolic diseases.…”
Section: Correlation Of Fat Metabolism With Cataractmentioning
confidence: 99%
“…In a Korean study ( 24 ), it was found that metabolism-associated fatty liver disease (MAFLD) was more closely associated with cataracts than non-alcoholic fatty liver disease (NAFLD). MAFLD may be a combined risk factor for cataracts, with significant correlations with all cataract subtypes because cataracts can be caused by various metabolic and inflammatory conditions, and MAFLD covers alcohol-induced cirrhosis and various metabolic diseases.…”
Section: Correlation Of Fat Metabolism With Cataractmentioning
confidence: 99%